Mini review: Peran fisiologis pati resisten sebagai substrat bakteri kolon dalam produksi asam lemak rantai pendek - Zalniati Fonna Rozali (Jurnal Bioleuser, 2024)
Resistant starch is a type of carbohydrate and is included in the raw materials or functional food ingredients that play a role in improving digestive health. Unlike starch, resistant starch cannot be hydrolyzed into glucose by the enzyme amylase in the small intestine, but it can act as dietary fiber, which is a substrate and fermented by saccharolytic bacteria in the colon. The main products of fermentation are short-chain fatty acids (SCFA) such as acetic acid, propionic acid, and butyric acid. The main fermentation of resistant starch is carried out by saccharolytic colonic microflora. The functional properties of resistant starch are often attributed to some metabolic effects of SCFAs at certain ratios in the gastrointestinal tract that benefit health, such as boosting immunity, reducing inflammation, and improving nutrient absorption. This literature review aims to present relevant research on the role of resistant starch as a substrate for saccharolytic bacteria in SCFA production in the colon.